Klasifikasi dan Perencanaan Persediaan Bahan Baku Kerajinan Kerang Mutiara Pada UD. Husein - N. E. Maitimu; M. L. Pattiapon; Luluk Ulandari (ARIKA, 2011)
UD. Husein is one of the small craft industry in the pearl oysters that if the craft is high art, including calligraphy patterned, Gethsemane, and Wild Horse.UD. Hussein to procure raw materials are still the traditional way or by virtue of estimates. Demand fluctuations over time lead to the need for inventory planning by forecasting future needs is used mendatang.Peramalan SeriesMoving Time Average and Exponential Smoothing.Tingkat Single items of interest can be seen from the critical level of goods, the use of speed or level of benefits that can be achieved and by capital absorption rate by classification ABC Analysis. Inventory planning of raw materials using Multi Item Inventory Model (FOI, FOQ and Combined). Results of research conducted can be seen that the largest capital absorbs pearl, profiles, velvet cloth and glass. Single exponential smoothing forecasting with Î± = 0.5 has an error value tekecil and inventory models have a combined total inventory costs at a minimum of one year with a frequency that is equal Rp. 41.502.500 optimal ordering 1 time / year in cost savings for raw materials inventory Rp.4.871 .650.